Barriers for Implementing the Hub and Spoke Model to Expand Medication for Opioid Use Disorder: A Case Study of Montana - Brandn Green; Danielle Christine Rhubart; Matthew R Filteau (SAGE Publishing, 2021)
Purpose: Access to medication for opioid use disorder (MOUD) varies across the rural-urban continuum. The Hub & Spoke Model (H&S) emerged to address these gaps in service whereby hubs with staff expertise in MOUD support delivery of specialized care to a network of spoke locations, often located in rural communities with workforce shortages. This paper presents a case study of efforts to implement the hub and spoke model in a frontier and rural (FAR) state: Montana. Methods: The primary data are structured interviews with 65 MOUD program staff in hub and spoke locations within Montana. Both inductive and deductive coding were used to analyze the transcripts. Findings: Using the H&S structure to expand access to MOUD in Montana led to mixed results. There were consistent themes identified in the interviews about the reasons why hubs struggled to successfully recruit spokes, including (1) geographic barriers, (2) a lack of interest among medical providers, (3) fears about excessive demand, (4) concerns about the financial viability of the model, and (5) a preference for informal technical assistance rather than a formal H&S relationship. In addition to these 5 themes, efforts to implement H&S across different medical systems were unsuccessful, whereas the H&S model worked more effectively when H&S locations were within the same organization. Conclusion: This case study identified limits to the H&S model utility in supporting states' abilities to expand access to MOUD treatment and offers suggestions for adapting it to accommodate variation across divergent rural contexts. We conclude with recommendations for strategies that may assist in expansion of MOUD in rural communities that are like those found in Montana.